2014
DOI: 10.1097/inf.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Complications of in utero Maternal HIV and Antiretroviral Exposure in HIV-exposed Infants

Abstract: Background Despite a wide body of literature supporting the use of antenatal antiretrovirals (ARV) for the prevention of mother to child transmission, there remains a need for continued monitoring as the intrauterine interval is a critical period during which fetal programming influences the future health and development of the child. Methods We conducted a systematic review of the current literature addressing potential metabolic complications of in utero HIV and ARV exposure. We describe studies evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…For example, studies in rhesus macaques exposed in utero to high doses of tenofovir showed reduced levels of insulin-like growth factor-1 (IGF-1) and reduced intrauterine growth. 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, studies in rhesus macaques exposed in utero to high doses of tenofovir showed reduced levels of insulin-like growth factor-1 (IGF-1) and reduced intrauterine growth. 7 …”
Section: Discussionmentioning
confidence: 99%
“…7 In a Canadian cohort of HEU infants exposed to cART in utero plasma lactate levels were increased during the first 6 months of life, 25 possibly as a consequence of mitochondrial toxicity that may persist for several years. 26 Many pathways of intermediary metabolism, including fatty acid oxidation, organic acid metabolism and amino acid metabolism, depend on normal oxidative phosphorylation and could therefore be affected by mitochondrial toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to avert the potential for major physical harm such as in the case of diethylstilboestrol exposure, disclosure is necessary in order to properly monitor HEU individuals into adulthood. Second, one could argue that in addition to childhood malignancies [16,17,23,36,37], there are a myriad of concerning data already surrounding malignancies as well as the mitochondrial [3844], mental [4547], bone [48–51], cardiovascular [52–54] and metabolic [5557] health in HEU children as described herein.…”
Section: Discussionmentioning
confidence: 99%